Desarrollo e implementación de un sistema de valoración de puntos y competencias a nivel administrativo en Plywood Ecuatoriana S. A. - Castellanos Reyes, Mónica Elena (2007)
The functions of the HR department is based on available information regarding jobs, these are the fundamental aspect of the productivity of the organization being proactive by using methods that sometime in the past left behind, for this reason aims companies to develop the assessment of charges for jobs that will enhance efficiency and effectiveness of human resource. This proposal includes the development and implementation of a system for assessing charges for items and skills in administration.